Muscle biopsy: what and why and when?. Issue 5 (5th June 2020) - Walters, Jon; Baborie, Atik
Abstract : Skeletal muscle biopsy remains an important investigative tool in the diagnosis of a variety of muscle disorders. Traditionally, someone with a limb-girdle muscle weakness, myopathic changes on electrophysiology and raised serum creatine kinase (CK) would have a muscle biopsy. However, we are living through a genetics revolution, and so do all such patients still need a biopsy? When should we undertake a muscle biopsy in patients with a distal, scapuloperoneal or other patterns of muscle weakness? When should patients with myositis, rhabdomyolysis, myalgia, hyperCKaemia or a drug-related myopathy have a muscle biopsy? What does normal muscle histology look like and what changes occur in neurogenic and myopathic disorders? As with Kipling's six honest serving men, we hope that by addressing these issues we can all become more confident about when to request a muscle biopsy and develop clearer insights into muscle pathology.